Sectarianism in Gilgit-Baltistan: An Analytical Study - Iftikhar, Gohar Ali; Hussain, Muntazir (Journal of Research in Humanities, 2023)
Gilgit-Baltistan, a Northern Pakistani region, is the study's focus. This paper investigates the historical, social, and political factors contributing to sectarian violence in the area, including the role of ethnic and religious identities, geopolitical dynamics, and state policies. The research draws on various sources, including media reports, academic studies, and videos. The paper argues that sectarianism in Gilgit-Baltistan is a multifaceted and multidimensional phenomenon that requires a nuanced understanding of local contexts and dynamics. The paper concludes by offering recommendations for policymakers and community leaders to address the root causes of sectarianism and promote peaceful coexistence in the region.